PENGARUH PARTISIPASI ANGGARAN, KOMITMEN ORGANISASI, KEPUASAN KERJA, JOB-RELEVANT INFORMATION DAN BUDAYA ORGANISASI TERHADAP KINERJA MANAJERIAL PADA PERHOTELAN DI PROVINSI RIAU - Apriansyah, Ginanjar; ', Zirman; ', Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study was conducted to analyze the Effects of budgetary participation, organizational commitment, job satisfaction, job-relevant information and organizational culture on managerial performance. The population of this study is that there are hotel services firm in the province of Riau. The methods used to collect primary data through a survey method. Data research conducted using a survey method by distributing.36 hotel managers who meet the criteria as a sample. This hypothesis was tested using multiple regression. The results of this study indicate that the variable budget participation, job satisfaction, and job-relevant information had no significant effect on the performance manajerial.variabel organizational commitment and organizational culture influence on managerial performance.Keywords: budget participation, Organizational Commitment, Job Satisfaction, job-relevant information, organizational culture, managerial performance